Extracellular vesicle-packaged circBIRC6 from cancer-associated fibroblasts induce platinum resistance via SUMOylation modulation in pancreatic cancer - Shangyou Zheng; Qing Tian; Yuan Yuan; Shuxin Sun; Tingting Li; Renpeng Xia; Rihua He; Yuming Luo; Qing Lin; Zhiqiang Fu; Yu Zhou; Rufu Chen; et al. (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Cancer-associated fibroblasts (CAFs) play pivotal roles in chemoresistance of pancreatic ductal adenocarcinoma (PDAC). However, the underlying mechanisms are poorly understood. Revealing the cross-talk network between tumor stroma and pancreatic cancer and developing effective strategies against oxaliplatin resistance are highly desired in the clinic. Methods High-throughput sequence was used to screened the key circRNAs transmitted by extracellular vesicles (EVs) from CAFs to pancreatic cancer cells. The associations between EV-packaged circBIRC6 and chemotherapy responsiveness were validated in a cohort of 82 cases of advanced PDAC patients. Then, the effects of EV-packaged circBIRC6 on CAF-induced oxaliplatin resistance were investigated by flow cytometry, colony formation, viability of pancreatic cancer organoids in vitro and by xenograft models in vivo. RNA pulldown, RNA immunoprecipitation, and sites mutation assays were used to reveal the underlying mechanism. Results We identified a circRNA, circBIRC6, is significantly upregulated in CAF-derived EVs and is positively associated with oxaliplatin-based chemoresistance. In vitro and in vivo functional assays showed that CAF-derived EV-packaged circBIRC6 enhance oxaliplatin resistance of pancreatic cancer cells and organoids via regulating the non-homologous end joining (NHEJ) dependent DNA repair. Mechanistically, circBIRC6 directly binds with XRCC4 and enhanced the interaction of XRCC4 with SUMO1 at the lysine 115 residue, which facilitated XRCC4 chromatin localization. XRCC4K115R mutation dramatically abrogated the EV-packaged circBIRC6 induced effect. Moreover, combination of antisense oligonucleotide inhibitors against circBIRC6 with Olaparib dramatically suppressed chemoresistance in patient-derived xenograft models. Conclusions Our study revealed that EV-packaged circBIRC6 confer oxaliplatin resistance in PDAC by mediating SUMOylation of XRCC4, introducing a promising predictive and therapeutic target for PDAC on oxaliplatin resistance.